The relationship between vocabulary learning strategies and the score of vocabulary levels test among undergraduate students in Universiti Teknologi Malaysia - Tan, Fui Teng (2021)
The present research study was an attempt to determine the vocabulary learning strategy preferences among UTM undergraduate students. It also determined the relationship between their vocabulary learning strategy use and the score of vocabulary levels test. To this end, 100 UTM undergraduate students were selected as the participants of the study based on convenience sampling at Universiti Teknologi Malaysia (UTM). The instrument used in the current research study was Vocabulary Learning Strategies Questionnaire which consisting of five different categories of vocabulary learning strategies. The other instrument was Nation’s vocabulary levels test which assessed the learners’ lexical knowledge in term of score base. In order to address the research questions, Pearson Correlation was conducted. The results revealed that the most frequently used vocabulary learning strategy subgroup was Determination Strategy and the least frequent one was Social Strategy. Besides, no significant correlation was found between the score of vocabulary levels test and vocabulary learning strategies. The important implication of the study is that students are necessary to have the awareness of vocabulary learning strategies used in order for them to develop their score of vocabulary levels test more easily and effectively.